2021
DOI: 10.1155/2021/8833221
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Restricted Knee Extension on Ground Reaction Force and Trunk Acceleration during Walking

Abstract: Gait parameters calculated from trunk acceleration reflect the features of gait; however, they cannot evaluate the gait pattern corresponding to the gait cycle. This study is aimed at investigating the differences in gait parameters calculated from trunk acceleration during gait corresponding to the gait cycle in healthy subjects with restricted knee extension. Participants included eight healthy volunteers who walked normally (NW) and with knee orthosis that restricted knee extension (ER). The ground reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Knee joint restriction, which is expected to be encountered in the gait cycle of individuals with LLD where the longer leg tends to shorten during the stance phase, may eventually increase the ground reaction forces exerted, especially on the midfoot area of the LLS. Previous studies indirectly confirm our observations as they have shown that similar artificially induced restrictions in the knee joint flexion (or extension) increase peak ground reaction forces during walking [61,62]. These changes have been observed in both the limb with restricted and the contralateral limb with unrestricted movement of the knee joint at distinct phases of gait, although significant differences were found only for initial contact [61].…”
Section: Effects Of Lld On Grfssupporting
confidence: 91%
See 1 more Smart Citation
“…Knee joint restriction, which is expected to be encountered in the gait cycle of individuals with LLD where the longer leg tends to shorten during the stance phase, may eventually increase the ground reaction forces exerted, especially on the midfoot area of the LLS. Previous studies indirectly confirm our observations as they have shown that similar artificially induced restrictions in the knee joint flexion (or extension) increase peak ground reaction forces during walking [61,62]. These changes have been observed in both the limb with restricted and the contralateral limb with unrestricted movement of the knee joint at distinct phases of gait, although significant differences were found only for initial contact [61].…”
Section: Effects Of Lld On Grfssupporting
confidence: 91%
“…Previous studies indirectly confirm our observations as they have shown that similar artificially induced restrictions in the knee joint flexion (or extension) increase peak ground reaction forces during walking [61,62]. These changes have been observed in both the limb with restricted and the contralateral limb with unrestricted movement of the knee joint at distinct phases of gait, although significant differences were found only for initial contact [61]. The fact that the GRFs exerted on midfoot areas of both feet were progressively increased as LLD increased may also be related to the greater pronation and supination expected to be presented by the LLS and SLS foot, respectively, during walking [33], as has been shown in individuals with asymptomatic pronated and supinated feet [63].…”
Section: Effects Of Lld On Grfssupporting
confidence: 89%
“…Kinetic changes during walking with a restricted extension of the knee joint have been analysed in previous studies where knee joint force was bilaterally increased during loading response depending on the degree of restriction of the knee joint [11][12][13]. Knee extension restriction also increases the vertical component of ground reaction force and the external knee flexion moment, which increases the demand for muscle activity in the lower extremities [14][15][16][17]. Gait kinematics and kinetics due to restriction of knee extension might increase the load on the lumbar region during the loading response phase of the restricted lower limb during gait and is related to low back pain.…”
Section: Introductionmentioning
confidence: 99%